CATALYTIC ACTIVITY TEST OF MO-V-TE-NB-OXIDE IN AMMOXIDATION OF PROPANE TO ACRYLONITRILE - Widi, Restu Kartiko (CHEMISTRY PROGRESS, 2014)
The ammoxidation of propane has been investigated at a multicomponent oxidic, MoVTeNb catalyst in the temperature of 673 K. The catalyst was prepared by sol-gel method, and dried by spray dried method. The activity test of the catalyst has been carried out using micro reactor and showed that it was active for ammoxidation of propane to acrylonitrile.   Keywords : ammoxidation, propane, mixed metal oxide catalyst, acryilonitrile